2010
DOI: 10.1039/c0ib00012d
|View full text |Cite
|
Sign up to set email alerts
|

Is there anyone out there?—Single-molecule atomic force microscopy meets yeast genetics to study sensor functions

Abstract: The ability to react to environmental stress is a key feature of microbial cells, which frequently involves the fortification of their cell wall as a primary step. In the model yeast Saccharomyces cerevisiae the biosynthesis of the cell wall is regulated by the so-called cell wall integrity signal transduction pathway, which starts with the detection of cell surface stress by a small family of five membrane-spanning sensors (Wsc1-Wsc3, Mid2, Mtl1). Although genetic evidence indicated that these proteins act as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 68 publications
(86 reference statements)
0
19
0
Order By: Relevance
“…On the one hand, this finding is not surprising since Wsc2 is lacking a cytosolic tail and it was previously shown that the cytosolic tail of ScWsc1 is essential for signal transduction (Lodder et al ., 1999; Straede and Heinisch, 2007). On the other hand, GFP‐tagged Wsc2 localizes to the plasma membrane and it was suggested that the WSC domains might mediate specific protein–protein interaction, thereby supporting, for example, the function of other CWI sensors (Heinisch and Dufrêne, 2010). Thus, a contribution to CWI signalling appeared conceivable but experimentally not provable.…”
Section: Discussionmentioning
confidence: 99%
“…On the one hand, this finding is not surprising since Wsc2 is lacking a cytosolic tail and it was previously shown that the cytosolic tail of ScWsc1 is essential for signal transduction (Lodder et al ., 1999; Straede and Heinisch, 2007). On the other hand, GFP‐tagged Wsc2 localizes to the plasma membrane and it was suggested that the WSC domains might mediate specific protein–protein interaction, thereby supporting, for example, the function of other CWI sensors (Heinisch and Dufrêne, 2010). Thus, a contribution to CWI signalling appeared conceivable but experimentally not provable.…”
Section: Discussionmentioning
confidence: 99%
“…It should also be noted that similar AFM approaches could be applied to study any cell surface proteins that can be elongated to penetrate the yeast cell wall (e.g., the pheromone receptors) and also for the investigation of basically any cell surface protein in other organisms (33).…”
Section: Quo Vadis?mentioning
confidence: 99%
“…This leads to conformational changes in the CRD, stabilized by disulfide bridges, and triggers both sensor clustering and conformational changes in the cytoplasmic domain, which then interacts with the downstream CWI components. The assembly of sensors in plasma membrane microdomains that recruit intracellular signaling components thus leads to the formation of a Wsc1 sensosome and enhances CWI signaling capacity (33). Wsc1 is depicted as a plasma membrane-spanning sensor that clusters upon the application of cell surface stress.…”
Section: Sensor Distribution and Functionmentioning
confidence: 99%
“…Therefore, the control mechanisms for its remodelling during growth and upon extracellular stress have drawn considerable attention in the past two decades, as reviewed in [26,28,29]. The signal transduction pathway (called the CWI pathway, for cell wall integrity) involved in this process has also been extensively reviewed [16,17,29]. A simplified scheme of its central components is presented in Figure 1.…”
Section: Introductionmentioning
confidence: 99%